Characteristics of Myopic Patients as a Guide for General Public at Rumah Sakit Islam Siti Rahmah Padang in 2021 - Haves Ashan; Zikra Apriani; Nurwiyeni Nurwiyeni; Seres Triola (Budapest International Research and Critics University, 2022)
Myopia is a form of refractive error in which rays parallel to the line of sight in the non-accommodating eye are focused in front of the retina. Refractive errors are one of the most common causes of visual impairment worldwide and the second leading cause of treatable blindness. Myopia as a refractive disorder, almost always occupies the top order compared to other refractive disorders. The purpose of this research is toknowing the characteristics of myopic patients at Siti Rahmah Hospital Padang in the period 2021. This study is descriptive with a case series design, the study population is myopia sufferers as many as 329 cases and the sample size is all of these cases.And the results of this study explain that the highest proportion of myopia sufferers is in the age group of 16 - 30 years, which is 165 people or 50.2%, myopia is mostly suffered by women, namely 185 people or 56.2%, while men 144 people or 43 ,8%, most of the patients examined were of the Karo ethnicity, amounting to 137 people (41.6%), that there were many myopia sufferers at the education level of Public High School which amounted to 157 people (47.7%), the percentage of myopia sufferers was The highest percentage was found in the sample who had a job as a student as many as 136 people (41.6%), and the highest percentage of myopia correction results was found in the sample with a full correction of 215 people (65.3%) while 114 people with a percentage of 34, 7% is the result of incomplete correction.